THE ROLE OF USING IG AND YOUTUBE AS MEDIA TO EXPLORE THE ENGLISH ABILITY OF AKBID BY BUNDA HUSADA BUNDA HUSADA STUDENTS - Puput Puspito Rini (Jurnal Ilmiah Global Education, 2023)
This study aimed to determine the role of Instagram and Youtube in exploring English skills for Akbid Karya Bunda Husada students. This research is qualitative. They use interview data collection techniques from 25 Akbid Karya Bunda Husada student informants in one class group. The study's results stated that; 1) Instagram and Youtube contain content containing interesting English learning materials in the form of videos, images, and writings.   Instagram and Youtube support the student learning process more fun and contribute to encouraging students' interest in learning; 2) The majority of students' perceptions say they strongly agree that Instagram and Youtube as interesting media are used in English learning. Not only used to collect material, Instagram and Youtube have become media for students to pour their creativity, skills, and English skills through assignment projects from lecturers; 3) students of Akbid Karya Bunda Husada need English to be able to compete in the era of globalization related to their skills, such as communicating, reading English literature, adding insight into discoveries, improving service, and the opportunity to get a good career.